2019
DOI: 10.1002/ca.23314
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of 3D ultrasound to MRI for the measurement and estimation of gastrocnemius muscle volume in adults and young people with and without cerebral palsy

Abstract: Muscle volume (MV) is an important parameter for understanding muscle morphology and adaptations to training, growth and pathology. In this study, we assessed the validity of freehand 3D ultrasound (3DUS) for measuring medial gastrocnemius MV in adults, typically developing (TD) children and children with cerebral palsy (CP). We also assessed the validity between our direct measures of MV and estimates derived from anatomical cross sectional area (ACSA) and muscle length (ML), using previously outlined methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 22 publications
(30 reference statements)
0
39
0
Order By: Relevance
“…Studies were categorized as observational ( n =45 cross‐sectional, 28–31,33–59,83–90,94,95,97,98,105,106 and n =1 longitudinal), 32 experimental ( n =25), 60–78,91,92,99–101,107 or methodology studies ( n =9) 79–82,93,96,102–104 (Table S2). Of the 25 intervention studies, 60–78,91,92,99–101,107 21 studies used musculoskeletal imaging as an outcome measure after a single intervention: botulinum neurotoxin‐A (BoNT‐A) ( n =6), 76,78,91,99,101,107 strength training ( n =3), 62,71,73 neuromuscular electrical stimulation ( n =3), 63,77,92 surgery ( n =2), 60,72 stretching ( n =2), 45,61 gait training (walk‐run) ( n =1), 65 vibration training ( n =1), 64 an aquatic programme ( n =1), 68 ankle bracing ( n =1), 66 and balance training ( n =1) 100 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies were categorized as observational ( n =45 cross‐sectional, 28–31,33–59,83–90,94,95,97,98,105,106 and n =1 longitudinal), 32 experimental ( n =25), 60–78,91,92,99–101,107 or methodology studies ( n =9) 79–82,93,96,102–104 (Table S2). Of the 25 intervention studies, 60–78,91,92,99–101,107 21 studies used musculoskeletal imaging as an outcome measure after a single intervention: botulinum neurotoxin‐A (BoNT‐A) ( n =6), 76,78,91,99,101,107 strength training ( n =3), 62,71,73 neuromuscular electrical stimulation ( n =3), 63,77,92 surgery ( n =2), 60,72 stretching ( n =2), 45,61 gait training (walk‐run) ( n =1), 65 vibration training ( n =1), 64 an aquatic programme ( n =1), 68 ankle bracing ( n =1), 66 and balance training ( n =1) 100 .…”
Section: Resultsmentioning
confidence: 99%
“…Three studies 67,74,75 used musculoskeletal imaging as an outcome measure after a combination of interventions – BoNT‐A plus strength training (compared to a BoNT‐A control period), 75 functional training plus neurodevelopmental treatment (compared to neurodevelopmental treatment group), 67 and neuromuscular electrical stimulation plus strength training (compared to a strength training only group) 74 – and one study compared outcomes of a stretching intervention with treadmill training 69 . Nine studies focused on methodological aspects of musculoskeletal imaging as a measurement tool in CP muscle 79–82,93,96,102–104 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The following outcomes were assessed on the participant’s affected leg in the case of unilateral CP, the most affected leg in the case of bilateral CP, or the right leg if a participant reported that both sides were equally affected. Achilles tendon cross‐sectional area and medial gastrocnemius muscle volume were assessed using a three‐dimensional freehand ultrasonography method 22 . Change in medial gastrocnemius muscle length was measured with a combination of 3D motion analysis and 2D ultrasound 14 .…”
Section: Methodsmentioning
confidence: 99%
“…All morphological (muscle volume and anatomical cross‐sectional area) and architectural measures (fascicle length and fascicle angle) were taken on the VL muscle and measured using a 3D ultrasound method, 30 Macgillivray et al 31 . For this method, a rigid body of four markers is secured to the handle of an ultrasound probe.…”
Section: Methodsmentioning
confidence: 99%